Five-degree-of-freedom robust control of a magnetic endoscopic capsule using an electromagnetic system. (May 2023) - Sadeghi Boroujeni, Pouria; Nejat Pishkenari, Hossein; Amiri Chimeh, Hadiseh; Moradi, Hamed; Vossoughi, Gholamreza
Abstract: Capsule endoscopy is a minimally invasive gastrointestinal diagnostic procedure. The active endoscopic capsule enables the physician to steer the device to any desired position and direction, resulting in a better diagnosis of the disease. Due to the model uncertainties and the existence of disturbances in the gastrointestinal system, traditional control methods cannot achieve robust performance and stability. To overcome this issue, in this paper, a robust sliding mode controller is proposed for 5 Degrees Of Freedom (DOF) control (3-DOF closed-loop control for position and 2-DOF open-loop control for orientation) of the capsule endoscope using an electromagnetic actuation system. The efficiency of the proposed control method is compared with a Proportional–Integral–Derivative (PID) controller considering the model uncertainties and external disturbances. The results of simulations considering 5% of uncertainty in the model parameters show that the suggested approach can precisely and efficiently actuate the capsule to follow the desired trajectory, with position and orientation accuracy of 0.53 mm and 0.69 degree, respectively. Experiments demonstrate the efficiency of the proposed controller, revealing a tracking error of about 0.73 mm in the capsule position. Furthermore, it has been proven by experiments that even in the presence of external disturbances, the proposed control system performs very well and keeps the capsule on the desired trajectory. Graphical abstract: Highlights: A sliding-mode controller is developed for control of a magnetic endoscopic capsule. The proposed controller is robust against model uncertainty and external disturbances. The superior performance of the proposed controller compared to PID is demonstrated. The control system efficacy is shown both in simulations and experiments. The proposed controller is optimal since it minimizes energy consumption.